Septal myocardial scar burden predicts the response to cardiac contractility modulation in patients with heart failure - Ansari, Uzair; Overhoff, Daniel; Burkhoff, Daniel; Fastner, Christian; Yücel, Gökhan; Röger, Susanne; Rudic, Boris; Liebe, Volker; Borggrefe, Martin; Akın, Ibrahim; Kuschyk, Jürgen; Papavassiliu, Theano; et al. (Scientific reports, 2022)
We hypothesized that myocardial septal scarring, assessed by cardiac magnetic resonance (CMR) using late gadolinium enhancement (LGE), at the site of cardiac contractility modulation (CCM) lead placement may predict treatment response. Eligible heart failure (HF) patients underwent LGE CMR imaging before CCM device implantation. The response to CCM therapy at follow-up was determined by a change in NYHA class and echocardiographic left ventricular ejection fraction (LVEF) assessment. Patients were classified as responders, if they showed an improvement in either NYHA class or improvement of LVEF by ≥ 5%. 58 patients were included. 67% of patients were classified as responders according to improved NYHA; 55% according to LVEF improvement. 74% of patients were responders if either NYHA class or LVEF improvement was observed. 90% of responders (according to NYHA class) showed septal LGE < 25% at septal position of the leads, while 44% of non-responders showed septal LGE > 25% (p < 0.01). In patients treated with CCM, an improvement of NYHA class was observed when leads were placed at myocardial segments with a CMR- LGE burden less than 25%.
Gesehen am 03.07.2023